2018
DOI: 10.1016/j.yrtph.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of manufactured nanomaterials - Characterisation and relevant methods. An outlook based on the OECD Testing Programme

Abstract: Identifying and characterising nanomaterials require additional information on physico-chemical properties and test methods, compared to chemicals in general. Furthermore, regulatory decisions for chemicals are usually based upon certain toxicological properties, and these effects may not be equivalent to those for nanomaterials. However, regulatory agencies lack an authoritative decision framework for nanomaterials that links the relevance of certain physico-chemical endpoints to toxicological effects. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 40 publications
2
89
0
2
Order By: Relevance
“…Regarding the PC properties identified as relevant in grouping approaches reported in this review and the need to justify a grouping hypothesis based on similarity, it is interesting to point out that the Working Party on Manufactured Nanomaterials (WPMN) (OECD, 2009) concluded that only 4 out of 22 test guidelines for measuring PC properties are applicable to NMs. In the last 10 years progress has been made in terms of identification of relevant PC properties and SOP development as thoroughly described by the ProSafe project (Rasmussen et al 2018; Steinh€ auser and Sayre 2017) which presents an up-to-date selection of PC properties and the preferred methods available for their measurement. The availability of SOPs for measuring PC properties is key to have a dataset of comparable measurements for model development, including grouping for read-across.…”
Section: Research Gapsmentioning
confidence: 99%
“…Regarding the PC properties identified as relevant in grouping approaches reported in this review and the need to justify a grouping hypothesis based on similarity, it is interesting to point out that the Working Party on Manufactured Nanomaterials (WPMN) (OECD, 2009) concluded that only 4 out of 22 test guidelines for measuring PC properties are applicable to NMs. In the last 10 years progress has been made in terms of identification of relevant PC properties and SOP development as thoroughly described by the ProSafe project (Rasmussen et al 2018; Steinh€ auser and Sayre 2017) which presents an up-to-date selection of PC properties and the preferred methods available for their measurement. The availability of SOPs for measuring PC properties is key to have a dataset of comparable measurements for model development, including grouping for read-across.…”
Section: Research Gapsmentioning
confidence: 99%
“…[ 10 ] As a result, an OECD Test Guidelines Programme is active for producing new and improved characterization methods for the detection of nanomaterials in complex matrices, for properties related to their fate and toxicological activity in the environment, with the contribution of Horizon 2020 funded projects. [ 11–14 ]…”
Section: Nanocharacterization and Risk Assessmentmentioning
confidence: 99%
“…Recent reviews and publications have identified bottlenecks and challenges in the field of nanocharacterization, [ 2,11,18–22 ] which are discussed briefly. More specifically, the surface‐oriented characterization needs to be developed, and it is critical for attaining a systematic collection of reactive descriptors such as hydration energies, production of reactive oxygen species that would provide more relevant toxicological information.…”
Section: Nanocharacterization and Risk Assessmentmentioning
confidence: 99%
“…Several unresolved issues remain, in particular the adequate physico-chemical characterization of nanoform(s) (Rasmussen et al 2018). Furthermore, clarification is needed regarding what specific data for NMs is necessary to fulfill the (new) REACH information requirements.…”
Section: Registration Evaluation Authorisation and Restriction Of Cmentioning
confidence: 99%